BAGAIMANA PANDANGAN ISLAM TERHADAP TRANSAKSI ARISAN?: SEBUAH STUDI LITERATUR - Ghofar Taufik; Rohyana Nur Isnaeny; Uswatun Hasanah (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Abstract This study aims to examine arisan transactions in Indonesia from an economic perspective in general and an Islamic economic perspective in particular. Along with the development of times and culture, so do human needs. Man has been given freedom of worship, but with limited freedom. A wide variety of practices and transactions are evolving today to meet needs. One example of a practice that is commonly found in the community is social gathering. This type of research is qualitative research with a literature study approach. Data were obtained from articles and journals from pre-existing research. The results showed that arisan when viewed from its acquisition, there are two forms of arisan, namely arisan goods and arisan money. Based on an economic perspective, social gatherings can be a means of saving, helping business sustainability, and can also be used as a business strategy. Meanwhile, from an accounting perspective, arisan is interpreted as an investment activity with the motive of avoiding inflation. Islamic economics views arisan as a transaction that can be punished mubah (permissible) as long as it does not contain elements that do not contradict the principle of muamalah. Keywords: Arisan, Islamic Economics, Muamalah